2009
DOI: 10.1016/j.bbabio.2009.04.003
|View full text |Cite
|
Sign up to set email alerts
|

High resolution crystal structure of Paracoccus denitrificans cytochrome c oxidase: New insights into the active site and the proton transfer pathways

Abstract: The structure of the two-subunit cytochrome c oxidase from Paracoccus denitrificans has been refined using X-ray cryodata to 2.25 A resolution in order to gain further insights into its mechanism of action. The refined structural model shows a number of new features including many additional solvent and detergent molecules. The electron density bridging the heme a(3) iron and Cu(B) of the active site is fitted best by a peroxo-group or a chloride ion. Two waters or OH(-) groups do not fit, one water (or OH(-))… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
200
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(216 citation statements)
references
References 54 publications
16
200
0
Order By: Relevance
“…A similar situation was observed previously for proton uptake to the Q B site in photosynthetic reaction centers (38). Similarly, in the P. denitrificans CytcO water molecules were suggested to act as the K-pathway entry point instead of the Glu (39). With the Glu II 101Asp mutant CytcO the proton contact is reestablished.…”
Section: Discussionsupporting
confidence: 55%
“…A similar situation was observed previously for proton uptake to the Q B site in photosynthetic reaction centers (38). Similarly, in the P. denitrificans CytcO water molecules were suggested to act as the K-pathway entry point instead of the Glu (39). With the Glu II 101Asp mutant CytcO the proton contact is reestablished.…”
Section: Discussionsupporting
confidence: 55%
“…The alterations include movement of the heme a 3 porphyrin ring, its farnesyl tail, and helix VIII, as well as loss of a key water linking the D path to the active site and formation of a new water chain into the active site (3). These changes upon reduction were an unexpected finding because other structural studies of bacterial oxidases (12,31,32) have reported no change, and in the bovine CcO the changes are fewer and mainly involve different regions than those seen in RsCcO (33), with the exception of Ser425 (bov Ser382). The significance of our recent findings (3) is potentially profound, as they suggest a unique mechanism of gating of the two proton pathways.…”
Section: S142mentioning
confidence: 78%
“…Removal of the carboxyl at position 132 strongly inhibits enzyme activity (2% of wild-type RsCcO) and proton pumping (8). A chain of waters between D132 and E286 can be seen in the D pathway of high-resolution structures of aa 3 -type CcO (10)(11)(12). Computational studies and molecular dynamics simulations suggest that these waters may serve in both proton transfer and proton storage (13)(14)(15).…”
Section: Resultsmentioning
confidence: 99%
“…An equivalent H pathway is present but not continuous in bacterial CcOs, but mutations in this region show no effect on coupling (11,12). However, no structural changes have been seen in the bacterial D channel (7,13), and to date only changes in the K and H pathways have been discerned in structures of the Rb. sphaeroides CcO (7).…”
mentioning
confidence: 99%